Durability Investigation of Carbon Fiber Reinforced Concrete under Salt-Freeze Coupling Effect - Yongcheng Ji (MDPI AG, 2021)
In order to study the durability behavior of CFRP (carbon fiber reinforced polymer) reinforced concrete, three category specimens (plain, partially reinforced, and fully reinforced) were selected to investigate its performance variation concerning chlorine salt and salt-freeze coupled environment, which included the microscopic examination, the distribution of chloride ion concentration, and the compressive properties. By observing the microscopic of the specimens, the surface and cross-section corrosion deterioration was examined with increasing exposure time, and the physical behavior of CFRP and core concrete were discussed. The chloride ion diffusion test exerted that the chloride ion concentration in plain specimens is at least 200 times higher than that of fully reinforced specimens. Therefore, the effectiveness of CFRP reinforcement will be proved to effectively hinder the penetration of chloride ions into the core section. The formula of the time-dependent effect of concrete diffusivity with salt-freeze coupling effect was presented and its accuracy verified. A time-varying finite element model of chloride ion distribution was established by using ABAQUS software. It can be seen from the axial compression test that the strength loss rate of three categories of specimens was varied when subjected to the corrosion environment. Therefore, it is proved that CFRP reinforcement can effectively reduce the deterioration of the specimen’s mechanical properties caused by the exposure environment. The research results can provide technical reference for applying the CFRP strengthened concrete in a severe salt-freeze environment.